The integration of yoga breathing techniques in cognitive behavioral therapy for post-traumatic stress disorder: A pragmatic randomized controlled trial - Haller, Heidemarie; Mitzinger, Dietmar; Cramer, Holger (Frontiers in Psychiatry, 2023)
Introduction: In trauma-focused Cognitive Behavioral Therapy (TF-CBT), stabilization techniques are used before confrontation ones to increase stress/affect tolerance and thus effectiveness of CBT. This study investigated the effects of pranayama, meditative yoga breathing and breath holding techniques, as a complimentary stabilization technique in patients with post-traumatic stress disorder (PTSD). Methods: Seventy-four PTSD-patients (84% female, 44.2±13 years) were randomized to receive either pranayama at the beginning of each TF-CBT session or TF-CBT alone. The primary outcome was self-reported PTSD severity after 10 sessions of TF-CBT. Secondary outcomes included quality of life, social participation, anxiety, depression, distress tolerance, emotion regulation, body awareness, breath-holding duration, acute emotional reaction to stress, and adverse events (AEs). Intention-to-treat (ITT) and exploratory per-protocol (PP) analyses of covariance with 95% confidence intervals (CI) were performed. Results: ITT analyses revealed no significant differences on primary or secondary outcomes, except for breath-holding duration in favor of pranayama-assisted TF-CBT (20.81 seconds, 95%CI=13.05|28.60). PP analyses of 31 patients without AEs during pranayama revealed significantly lower PTSD severity (-5.41, 95%CI=-10.17|-0.64) and higher mental quality of life (4.89, 95%CI=1.38|8.41) than controls. In contrast, patients with AEs during pranayama breath holding reported significantly higher PTSD severity (12.39, 95%CI=5.08|19.71) than controls. Concurrent somatoform disorders were found to be a significant moderator of change in PTSD severity (p=0.029). Conclusion: In PTSD patients without concurrent somatoform disorders, the integration of pranayama into TF-CBT might reduce post-traumatic symptoms and increase mental quality of life more efficiently than TF-CBT alone. The results remain preliminary until they can be replicated by ITT analyses.